PENGALAMAN KLIEN KANKER PAYUDARA PASKA MASTEKTOMI PADA SUKU BATAK DI MEDAN - Lestari Lestari; Nani Zulfikar (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Breast removal affectsbody image and self image which potentially reduces sexual function and sexual attraction. In this condition and because cancer treatment can cause continuous stress, so that it not only affects physical adjustment but also individual psychological adjustment. The purpose of this study is to explore in depth how the client's perception of breast cancer after mastectomy in Batak tribe. This research was descriptive phenomenology study. Data was collected by in-depth interviews, and fieldnotes. Data that was obtained is analyzed by Colaizzi approach. The results of research analysis found 6 themes: (1) The experience of breast cancer client after undergoing mastectomy, (2) The experience of breast cancer client adapting to physical and psychological changes after mastectomy (3) The quality of life for post-mastectomy breast cancer clients, (4) Constraints that experienced by breast cancer clients after mastectomy, (5) The experience of post-mastectomy breast cancer client in Batak tribes and (6) The expectations of post-mastectomy breast cancer client. Based on the results of study it is recommended generally for breast cancer patients, the results of this study can be used as input / information material, keep trying and enthusiasm so that patients can further enhance their confidence and develop their own potential.